1973
DOI: 10.1139/p73-277
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Satellite Intensities and Triplet Splitting in the B3Σu State of S2

Abstract: Measurements have been made on the intensities of rotational satellites (AN # AJ) in selectively excited fluorescence in the B-X system of S2. The satellites appear in fluorescence emitted by the u' = 4 level but are absent in u' = 3 emission. Comparison of our results with line strengths calculated according to the formulation of Tatum and Watson shows that these two adjacent vibrational levels differ in the magnitude and sign of the triplet splitting constant. A reexamination of previous spectral analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The highly perturbed nature of the absorption and emission bands associated with these vibrational levels long hindered the development of a full spectroscopic analysis. Following earlier work by Meakin and Barrow, 17 Meyer and Crosley, 18 Patino and Barrow, 19 Matsumi et al, 20 and Heaven et al, 21 Green and Western 22,23 provided the first comprehensive rotational analysis of the B(0-9) levels. Their analysis was informed by a combination of new rotationally cold laserinduced fluorescence spectra, room temperature fluorescence spectra, and existing high-temperature (∼1000 K) absorption spectra from Barrow and co-workers, complemented by new radiative lifetime measurements and those of Matsumi et al 24 As first suggested by Meakin and Barrow, 17 the perturbing state has 3 Π u symmetry; it is now labeled as the B 3 Π u state.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The highly perturbed nature of the absorption and emission bands associated with these vibrational levels long hindered the development of a full spectroscopic analysis. Following earlier work by Meakin and Barrow, 17 Meyer and Crosley, 18 Patino and Barrow, 19 Matsumi et al, 20 and Heaven et al, 21 Green and Western 22,23 provided the first comprehensive rotational analysis of the B(0-9) levels. Their analysis was informed by a combination of new rotationally cold laserinduced fluorescence spectra, room temperature fluorescence spectra, and existing high-temperature (∼1000 K) absorption spectra from Barrow and co-workers, complemented by new radiative lifetime measurements and those of Matsumi et al 24 As first suggested by Meakin and Barrow, 17 the perturbing state has 3 Π u symmetry; it is now labeled as the B 3 Π u state.…”
Section: Introductionmentioning
confidence: 96%
“…Wheeler et al 25 report a rapid onset of broadening at v = 11, with widths maximizing at 14 cm −1 for B(13), followed by gradually decreasing widths, reaching 7 cm −1 for B (17). A second abrupt increase in width occurs at B (18), with the v = 18 and 19 levels having widths estimated by Wheeler et al 25 to be greater than 15 cm −1 and 20 cm −1 , respectively. A subsequent velocitymap imaging study of S( 3 P J ) photodissociation products, by Frederix et al, 26 led to a revised value for the lowest dissociation energy and clarification of the relevant dissociation channels for the B(10) and B(11) levels.…”
Section: Introductionmentioning
confidence: 96%
“…8 Many efforts have been made to perform deperturbation analyses, with the early work summarized by Barrow and Du Parcq. 9 Only after the supersonic free jet studies of Matsumi et al., 10,11 in which transitions to the B and B" states were distinguished, was a full assignment of the band system possible.…”
Section: Introductionmentioning
confidence: 99%
“…Using LIF, the relative intensities of the satellites and the main branches emitted by the single pumped level can be measured. In this case such ratios led to some new and surprising information concerning the spin-spin interaction in the B-state (2), which had escaped notice in earlier conventional spectroscopic studies.…”
Section: Lif Experimentsmentioning
confidence: 89%